2020
DOI: 10.1016/j.mattod.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity at 161 K in thorium hydride ThH10: Synthesis and properties

Abstract: Highlights• Superconductivity in fcc-ThH10 at 159-161 K at the pressure 174 Gigapascals • Very wide interval of stability of fcc-ThH10 from 85 to 185 GPa. • Upper critical magnetic field ThH10 ~45 Т. • Novel discovered superhydride hcp-ThH9 with TC of 146 K (170 GPa) and upper critical field ~38 Т • Newly discovered thorium hydrides: I4/mmm-ThH4 and Cmc21-ThH6 Abstract Here we report targeted high-pressure synthesis of two novel high-TC hydride superconductors, P63/mmc-ThH9 and 3 ̅ -ThH10, with the experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
225
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 260 publications
(246 citation statements)
references
References 54 publications
21
225
0
Order By: Relevance
“…Semenok et al [44] also reported on the discovery of another high-temperature superconducting phase of ThH 10 at P=174 GPa, which exhibitsFm m 3 crystallographic symmetry and superconducting transition temperature of T c =159 K. In figure 3 we show raw upper critical field, B c2 (T), data for this phase [44] and data fit to equations (3)- (6).…”
Section: Thh 10 (P=174 Gpa) In Uemura Plotmentioning
confidence: 87%
See 3 more Smart Citations
“…Semenok et al [44] also reported on the discovery of another high-temperature superconducting phase of ThH 10 at P=174 GPa, which exhibitsFm m 3 crystallographic symmetry and superconducting transition temperature of T c =159 K. In figure 3 we show raw upper critical field, B c2 (T), data for this phase [44] and data fit to equations (3)- (6).…”
Section: Thh 10 (P=174 Gpa) In Uemura Plotmentioning
confidence: 87%
“…Semenok et al [44] reported the discovery of a high-temperature superconducting phase of ThH 9 at P=170 GPa which exhibits P6 3 /mmc crystallographic symmetry and superconducting transition temperature of T c =146 K. They also performed first principles calculations and deduced the effective mass in this superconductor: As we mentioned in our previous papers [12,13,46,47], first principles calculations [39,48,49] always provide α-values near 5, which is the very strong-coupling limit for s-wave symmetry (also note that other superconducting gap symmetries have weak-coupling limits of α∼5 [50][51][52]). Despite the orthodox view, several new, alternative, approaches were developed to explain NRT superconductivity in compressed hydrides: Hirsch and Marsiglio [53], Souza and Marsiglio [54], Harshman and Fiory [55], as well as Kaplan and Imry [56].…”
Section: Thh 9 (P=170 Gpa) In Uemura Plotmentioning
confidence: 99%
See 2 more Smart Citations
“…
Recently, Troyan et al (2019 arXiv:1908 and Kong et al (2019 arXiv:1909 extended near-room-temperature superconductors family by new yttrium superhydride polymorphs, YHn (n = 4,6,7,9), which exhibit superconducting transition temperatures in the range of Tc = 210-243 K at pressure of P = 160-255 GPa. In this paper, temperature dependent upper critical field data, Bc2(T), for highly-compressed mixture of YH4+YH6 phases (reported by Kong et al 2019 arXiv:1909) is analysed to deduce the ratio of Tc to the Fermi temperature, TF.
…”
mentioning
confidence: 99%